Aplikasi Sistem Pakar Untuk Deteksi Autisme Pada Anak Berbasis Web - Elirza Halena; Noveri Lysbetti Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
In the case of children with autism, the role of parents is the most important thing, where parents can make early detection of the possibility of children autism by observing children's behavior in daily life. Surely it is facilitated by the application of expert systems to detect children autism. The application of expert systems is required by parents as a first step to monitor the development of the child without having to meet with experts directly, so parents can easily find out whether their children are autism detected or not.This Expert System Application is implemented into a web-based application with PHP programming language and MySQL database. By using expert knowledge and using certainty factor method in the calculation, then the final result from this Expert System Application is the conclusion of being at risk of autism, possibly autism or not risk of autism in children. In the final result, the value of expert beliefs from the calculation is obtained from the Certainty Factor Method. The result of validating testing is 100% on the test system functionality, and 100% on testing expert system with certainty factor method.Keywords : Application, autism, certainty factor, detection, expert system